Association ofIgpertension with diabetes mellitus - Ahmad H. Asdie Ahmad H. Asdie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1992)
The clinical impression of association between hypertension and diabetes mellitus has not been consistently confirmed by epidemiological studies. The variety of methodological problems in this area of research includes the choice of appropriate patients and control group, the measurement techniques used, and consideration of many possible confounding variables.Hypertension in diabetes mellitus patients contributes substantially to the increased cardiovascular morbidity and mortality, and should be actively treated as accurately as diabetes mellitus itself. The first therapeuticstep is reduction of overweight, saltintake, and stopsmoking; the omission of interfering drugs and adequate education. Prescription of diuretic drugs or alternatively of calcium antagonists, vasodilators of hydralazin or prazosin. The adds of minoxidil or cap topril to the previousdrugsshouldonlybe taken after evaluation of the overall situation. It should be kept in mind that all anti-hypertensive agents have disadvantages, some of them serious, when used for diabetic patients Key Words: diabetes mellitus - hypertension - cardiovascular mortality - anti-hypertensive treatment - overweight